A Varactor-Tunable Rasorber Using Tripole and Ring Slot Elements - Qingxin Guo; Qian Chen; Jianxun Su; Zengrui Li (International Journal of Antennas and Propagation)
In this study, a frequency-selective rasorber with a tunable passband and two absorptive bands is presented. It is designed using two active FSSs, an absorptive FSS realized with tripole elements, and a lossless bandpass FSS achieved with ring slots. Both active FSSs embedded with varactors realize the shift of transmission frequency bands by controlling the bias voltage of the feed network. The working principle is briefly investigated according to an equivalent circuit model. A prototype is fabricated and measured to verify the simulated results, which show that a passband is tuned from 3 to 4.78 GHz between two absorptive bands, and the maximum band of |S11| < −10 dB covers from 2.2 to 7.96 GHz.